Estudo sobre o uso do dispositivo leito de acolhimento noturno em Centro de Atenção Psicossocial Álcool e Drogas CAPS AD - Moura, Aline Silva de (2014)
This research aimed at investigating the device called " overnight-stay " in moment of crisis the user of alcohol and other drugs , in the context of a Psychosocial Care Center Alcohol and Drugs 24 ( CAPS ad III ) , in Campinas SP . It was intended to characterize the users who occupied overnight-stay according to demographic data, data on the use of psychoactive substances, data relating to the commencement CAPSad III as well as characterize the bed occupancy rates and indications of the team for their use. This is a descriptive cross-sectional study (April / 2012 to March / 2013), using research roadmap and documentary record data from four sources: medical records, insertion records in overnight-stay, books and bank shift changes data team. As a complementary source of information we used interview with service managers. Data were organized and analyzed from a computerized database using the Excel program. The research pointed out that the bed night shelter was occupied by 167 users 315 times, most males (77,25%), single (46,11%), aged between 31 and 40 (36,53%), incomplete elementary education (40,12%), unemployed (51,50%) and living with a family member (50,30%) . The demand for treatment was mainly due to the use of multiple drugs (53, 89%), especially if alcohol linked to another substance, followed by the exclusive use of alcohol (39,52%). Most cases (81,43%) had a comorbidity, particularly psychiatric (51,23 %). The length of enrollment in CAPSadII patients for 6 months (36,53%) and equipment for emergency care were the services most have referred users (30,43%). Among the indications for insertion into overnight-stay, include the promotion of abstinence (34, 85%), psychiatric stabilization (21,08%) and the need for protected environment (20,64%). Changes in mental examination were significant (66, 67%), especially mood changes (29, 97%) and insomnia (22, 67%). Significant portions of users were on the streets (34,13%) which requires other joints and need of supporting this vulnerable population. The logic of overnight-stay occupancy rates and indications of the team for their use were characterized. The overnightstay in CAPSad III , is seen as an opportunity to expand attention to the crisis the user of alcohol and other drugs in the anti-asylum logic , as they allow the regulation and care of the team. His newly deployment within the network of care to the user of alcohol and other drugs brings relevance to this investigation given the fact that it can contribute to a better understanding and characterization as well as for actiong planning.